Dynamic Pump-probe studies of TE and TM modes in semiconductor optical amplfiers - Bradley, Louise; Philippe, Severine; Landais, Pascal; Martinez-Rosas, Miguel; Surre, Frederick (My University, 2005)
A contra-propagation set up is implemented and dynamic pump probe studies of a InGaAsP/InP SOA in the gain regime are undertaken using pulses of 2ps duration. The time resolved amplified probe signal is measured separately for the TE and TM modes of the semiconductor optical amplifier. Different behaviours are observed both in the gain compression and the timescales of the effect, with the TM mode displaying a faster component and a higher gain compression.
Proceedings of SPIE, Opto-Ireland 2005: Optoelectronics, Photonic Devices, and Optical Networks
SPIE Opto-Ireland 2005
Keywords: Semiconductor optical amplifier; Optical switching; Gain; Polarisation; Pump-probe